Dampak COVID-19 Terhadap Kecepatan Penyesuaian Struktur Modal: Studi Perbandingan Antara Perusahaan Sharia-Compliant dan Non-Compliant di Indonesia - Karim, Abdul; Wulandari, Karina (UI Scholars Hub, 2025)
This study aims to examine the impact of the COVID-19 pandemic on capital structure adjustment among firms in Indonesia, with a focus on differences between Sharia-compliant and non-compliant companies. The research utilizes panel data from non-financial firms listed on the Indonesia Stock Exchange (IDX) during the 2017–2022 period. Capital structure adjustment is analyzed using panel regression methods, controlling for variables such as profitability, growth, firm size, tangibility, liquidity, and income volatility. The findings indicate that the pandemic increased leverage and accelerated capital structure adjustment overall. However, Sharia-compliant firms exhibited a slower adjustment speed compared to non-compliant firms, due to constraints imposed by Islamic financial principles. This study contributes to a deeper understanding of capital structure dynamics during crises and offers practical implications for corporate financial decision-making and regulatory strategies.